2023
DOI: 10.1146/annurev-publhealth-060220-041643
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Mobile Technology for Public Health Promotion: A Multidisciplinary Perspective

Abstract: Health behaviors are inextricably linked to health and well-being, yet issues such as physical inactivity and insufficient sleep remain significant global public health problems. Mobile technology—and the unprecedented scope and quantity of data it generates—has a promising but largely untapped potential to promote health behaviors at the individual and population levels. This perspective article provides multidisciplinary recommendations on the design and use of mobile technology, and the concomitant wealth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Mobile health apps are critical in public health by effectively disseminating evidence-based information to a wide audience, including underserved populations in remote areas [19]- [23]. These apps can raise awareness about preventive measures, screening guidelines, and disease management strategies through targeted health messages and educational content.…”
Section: Mobile Health Apps and Public Health Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile health apps are critical in public health by effectively disseminating evidence-based information to a wide audience, including underserved populations in remote areas [19]- [23]. These apps can raise awareness about preventive measures, screening guidelines, and disease management strategies through targeted health messages and educational content.…”
Section: Mobile Health Apps and Public Health Awarenessmentioning
confidence: 99%
“…Studies emphasize the importance of factors influencing user acceptance, such as digital literacy and privacy concerns, in shaping behavioral intentions towards mHealth apps [17], [18]. Additionally, user adherence to mHealth apps is influenced by personal characteristics, app design, and technical features, highlighting the need for continuous user engagement [19]. Leveraging mobile technology data can personalize interventions and promote health behaviors effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of Multi-disciplinary Technologies Advancement Hicks et al concluded that to establish evidence-based guidelines, progress must be made in personalizing interventions to an individual's social, cultural, and built environments and evaluating the relationships between mobile technology data and health. By reviewing these strategies and emphasizing future research directions, we promote using theory-based, personalized, and humancentered initiatives to encourage health behaviors (Hicks et al, 2023).…”
Section: Opportunities Imentioning
confidence: 99%
“…The use of mobile technology in promoting health has opportunities and challenges. The latter includes addressing barriers and drivers of health behaviors, high PGHD entry load, and loss of interest [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%